Maintenance Heavy Equipment Management Through Contract Models or Company it Self - Afiyuddin, Andi; Sudiarno, Adithya (Institut Teknologi Sepuluh Nopember, 2020)
One important activity and cause high costs in the company is maintenance and in mining one of critical maintenance is heavy equipment. Issue of manpower, skill, expert and equipment population made company can’t handle the maintenance it self. Agreement to the contractor made with several contract models. This maintenance management either by company it self or by different contract models have their strong and weakness point. This research will analyze which maintenance management is better using Fuzzy AHP as a multicriteria decision making tool. Responden will selected to define the criteria and sub-criteria. The result of this research are to select maintenance management that will use as standard in the company.